2020
DOI: 10.21203/rs.3.rs-114700/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time until treatment initiation is associated with catheter survival in peritoneal dialysis-related peritonitis

Abstract: Introduction: For peritonitis, a serious complication of peritoneal dialysis (PD), we investigated the relation between duration from the sign (PD effluent abnormalities) to treatment with appropriate antibiotics (ST time) and catheter removal. Design, setting, participants: For 62 PD hospital patients, data of PD-related peritonitis (n=109) were collected retrospectively. We examined ST time and PD catheter removal times using univariate and multivariate analyses.Results: The catheter removal rate in the dela… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…171 In another retrospective study of 109 peritonitis episodes, a delay of starting IP or intravenous antibiotics treatment from the sign of peritonitis by 24 h conferred a threefold risk of peritoneal catheter removal by multivariate analysis. 172 For logistics consideration, immediate IP antibiotic administration might not be feasible in the emergency department or wards in which staff are not familiar with PD. In order to avoid the adverse outcome of delayed peritonitis treatment, the systemic route should be started as a temporary measure when there is a foreseeable delay, such as long wait for dialysis unit bed or presentation outside the working hours of the ambulatory PD unit.…”
Section: Empiric Antibiotic Selectionmentioning
confidence: 99%
“…171 In another retrospective study of 109 peritonitis episodes, a delay of starting IP or intravenous antibiotics treatment from the sign of peritonitis by 24 h conferred a threefold risk of peritoneal catheter removal by multivariate analysis. 172 For logistics consideration, immediate IP antibiotic administration might not be feasible in the emergency department or wards in which staff are not familiar with PD. In order to avoid the adverse outcome of delayed peritonitis treatment, the systemic route should be started as a temporary measure when there is a foreseeable delay, such as long wait for dialysis unit bed or presentation outside the working hours of the ambulatory PD unit.…”
Section: Empiric Antibiotic Selectionmentioning
confidence: 99%
“…On the other hand, some patients applying antibiotics by themselves live far away from the PD center, and the remote distance from the hospital is also one of the risk factors for peritonitis and technique failure 21 . Moreover, in our study, the application of antibiotics was not standardized at home by PDAP patients, which delayed the optimal timing of standard treatment 17 and added to the di culty in cure.…”
Section: Discussionmentioning
confidence: 83%
“…For instance, a study found that PD duration less than 2.4 years was associated with a higher resolution rate than that longer than 2.4 years 16 . Another study indicated that a longer PD duration at the onset of peritonitis was related to a longer duration from PD e uent abnormalities to treatment with appropriate antibiotics, which further led to adverse outcomes 17 . Similar nding was also obtained from other study, which was that patients receiving long-term dialysis were prone to gram-negative bacterial infection and worse treatment outcomes compared with those undergoing short-term dialysis 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Although PD is suggested as an effective treatment modality for ESKD patients, peritonitis remains a major complication that might result in the discontinuation of the treatment (25). If the patient does not concern about cleanliness, it may lead to infection of the peritoneum, subcutaneous tunnel, and catheter exit site (4).…”
Section: Figure 2: the Procedures For Peritoneal Dialysismentioning
confidence: 99%